Practical considerations for managing patients with diabetes and dementia. Issue 6 (2nd November 2017) - Mair, Michelle L; Athavale, Rohin; Abdelhafiz, Ahmed H
ABSTRACT: Introduction : Diabetes and dementia appear to be linked epidemiologically and share a common pathogenetic mechanism. The development of dementia in older people with diabetes will have a significant impact on diabetes self-care and will increase the risk of hypoglycaemia and frailty which ultimately lead to disability and poor outcome. Areas covered : We performed a Medline and Embase search from 1997 to present on relevant dementia and diabetes studies published in English language. Expert commentary : Older people with comorbid diabetes and dementia are functionally heterogeneous and interventions should be proportionate to patients 'functional capacity. Metabolic targets can be tightened in fit persons and relaxed when cognitive abilities continue to decline and overall function deteriorates. A holistic multidisciplinary team approach that involves patients, their carers and integrated primary and secondary care services at one point of care that focuses on improving function and maintaining quality of life is needed.